Application of Samarium- and Terbium-Sensitized Luminescence via a Multivariate-Based Approach for the Determination of Orbifloxacin - Nessreen Al-Hashimi; Ahmed S. El-Shafie; Asmaa Jumaa; Marwa El-Azazy (Journal of Chemistry)
A lanthanide-based optical sensor has been developed for the sensitive and reliable spectrofluorometric determination of the fluoroquinolone antibiotic orbifloxacin (ORLX). Reaction of ORLX and two lanthanide metal ions, Sm(III) and Tb(III), in aqueous buffered solution produced highly fluorescent complexes. Plackett–Burman design (PBD) was used to explore the impact of four factors, pH, temperature (Temp), contact time (CT), and metal volume (MV), on the fluorescence intensity (FI) of the produced complexes. The obtained data showed that pH was the most significant variable. A blend of pH = 5.0, MV = 2.0 mL, T = 25°C, and CT = 10 min was used to achieve the maximum FI. FT-IR and Raman analyses were performed for the crystals of the as-prepared complexes. Obtained data showed shifting in most of the absorption bands, confirming the complexation of ORLX with both metal ions. Job’s method showed that the stoichiometry for the reaction of ORLX with Sm(III) and Tb(III) was 1 : 1. The proposed method was validated following the ICH guidelines. Injection formulation was analyzed successfully with the developed method with high recovery (99.42–100.91%). The detection and quantification limits were 0.987 and 3.289 ng/mL for the ORLX-Sm(III) complex and 1.020 and 3.399 ng/mL for the ORLX-Tb(III) complex, respectively.